Consumer literacy among college students - De Dios, Candice Marie F.
A description of the general level of consumer literacy among college students in Manila and Quezon City was presented. It described college students' knowledge of the basic provisions in the Consumer Act of the Philippines such as the price tag, labeling, packaging, sales promotion, warranty, food and drugs. The study also explored the association of consumer literacy to gender, year level, socio-economic status and consumer education background. Lastly, it showed the comparison of consumer literacy level of college students in terms of gender, year level, income, and consumer education background. Using post-test only design with non-equivalent comparison groups, 100 male and female college students from private and public schools whose ages range from 16-23, participated in the study. Convenience, and snowball sampling were utilized, getting fifteen students in seven schools. Item analysis, non-parametric statistics, chi-square, and descriptive statistics were used to analyze the gathered data. Results showed that more than half of the respondents have a satisfactory understanding of the provisions in the Consumer Act of the Philippines. However, there were still a considerable number of students who do not have a good grasp of the consumer laws and the needed consumer skills. In general, students do not know the rules on selling price, the required contents of the price tag, and proper labeling as indicated in the Consumer Act of the Philippines. Although students seem to know that products have warranties as they have difficulty in understanding some technical terms such as express, implied, and limited warranty under the rules of warranty. Of all the topics covered in the test, students know most of the provisions and functions of the packaging. It was also noticed that the students appear to be very attentive in learning consumer skills that are useful in reducing functional or physical risks. The study found no sufficient evidence to show that there is a difference in the consumer literacy levels between male and female, the high and low income groups, and those who have taken consumer education course from those who did not. The result, suggests that consumer education in schools is not helpful in improving these skills. There is, however, a significant difference in the consumer literacy among students with different year levels with more students in the second year level getting a passing score. Thus, this study suggests an aggressive consumer education campaign. There is also a need to update and develop existing consumer education courses. Aside from schools, concerned government agencies should also take the initiative to disseminate information and to protect consumers through efficient regulation of consumer-related laws. The business sector might likewise self-regulate to maintain or achieve desirable customer service. To further address the issue on consumer literacy, there is a need to have an evaluation of consumer education curriculum at all levels: elementary, high school, and college. It will also be interesting to conduct a research determining what year level consumer education should be taught that will result to a more effective retention of consumer literacy. A study on developing a course design appropriate and most useful for consumers within outside the formal school system will also be a valuable undertaking. Indeed, education should be one of the prime agents for improving consumer literacy and there is a need to ensure that this is adequately addressed.